Multifunctional selenium nanoparticles with Galangin-induced HepG2 cell apoptosis through p38 and AKT signalling pathway - Yinghua Li (Royal Society Open Science, 2018)
The morbidity and mortality of hepatocellular carcinoma, the most common cancer, are increasing continuously worldwide. Galangin (Ga) has been demonstrated to possess anti-cancer effect, but the efficacy of Ga was limited by its low permeability and poor solubility. To develop aqueous formulation and improve the anti-cancer activity of Ga, surface decoration of functionalized selenium nanoparticles with Ga (Se@Ga) was synthesized in the present study. The aim of this study was to evaluate the anti-cancer effect of Se@Ga and the mechanism on HepG2 cells. Se@Ga-induced HepG2 cell apoptosis was confirmed by depletion of mitochondrial membrane potential, translocation of phosphatidylserine and caspase-3 activation. Furthermore, Se@Ga enhanced the anti-cancer activity of HepG2 cells through ROS-mediated AKT and p38 signalling pathways. In summary, these results suggest that Se@Ga might be potential candidate chemotherapy for cancer.